Preparation, Characterization, And Computational Study Of Bimetallic Iron Oxide Based Catalyst For Catalytic Oxidative Desulfurization Of Model Diesel - Mohd Nazmi, Nor Atiq Syakila (2021)
Catalytic oxidative desulfurization (Cat-ODS) has been introduced as a new technique in achieving ultra-low sulfur diesel. In this study, Fe catalyst supported on alumina were prepared by wetness impregnation method and characterized using N2- adsorption/desorption (NA), field emission scanning electron microscopic (FESEM), X-ray diffraction (XRD) and High-Resolution Transmission Electron (HRTEM).